Quantitative Analysis of Colostrum Bacteriology on British Dairy Farms - Hyde, Robert M.; Green, Martin J.; Hudson, Chris; Down, Peter M. (Frontiers in Veterinary Science, 2020)
Total bacterial counts (TBC) and coliform counts (CC) were estimated for 328 colostrum samples from 56 British dairy farms. Samples collected directly from cows’ teats had lower mean TBC (32,079) and CC (21) than those collected from both colostrum collection buckets (TBC: 327,879, CC: 13,294) and feeding equipment (TBC: 439,438, CC: 17,859). Mixed effects models were built using an automated backwards stepwise process in conjunction with repeated bootstrap sampling to provide robust estimates of both effect size and 95% bootstrap confidence intervals (BCI) as well as an estimate of the reproducibility of a variable effect within a target population (stability). Colostrum collected using parlour (2.06 log cfu/ml, 95% BCI: 0.35 - 3.71) or robot (3.38 log cfu/ml, 95% BCI: 1.29 - 5.80) milking systems, and samples collected from feeding equipment (2.36 log cfu/ml, 95% BCI: 0.77 - 5.45) were associated with higher TBC than those collected from the teat, suggesting interventions to reduce bacterial contamination should focus on the hygiene of collection and feeding equipment. The use of hot water to clean feeding equipment (-2.54 log cfu/ml, 95% BCI: -3.76 - -1.74) was associated with reductions in TBC, and the use of peracetic acid (-2.04 log cfu/ml, 95% BCI: -3.49 - -0.56) or hypochlorite (-1.60 log cfu/ml, 95% BCI: -3.01 - 0.27) to clean collection equipment was associated with reductions in TBC compared with water. Cleaning collection equipment less frequently than every use (1.75 log cfu/ml, 95% BCI: 1.30 - 2.49) was associated with increased TBC, the use of pre-milking teat disinfection prior to colostrum collection (-1.85 log cfu/ml, 95% BCI: -3.39 - 2.23) and the pasteurisation of colostrum (-3.79 log cfu/ml, 95% BCI: -5.87 - -2.93) were associated with reduced TBC. Colostrum collection protocols should include the cleaning of colostrum collection and feeding equipment after every use with hot water as opposed to cold water, and hypochlorite or peracetic acid as opposed to water or parlour wash. Cows’ teats should be prepared with a pre-milking teat disinfectant and wiped with a clean, dry paper towel prior to colostrum collection, and colostrum should be pasteurised where possible.